(untitled) (Journal of the College of Basic Education, 2022)
The aim of the research is to use an educational design according to the dimensions of human development and its impact on the scientific culture of middle school students and their skillful thinking. To achieve this, the following two null hypotheses were developed There are no statistically significant differences at the level of [significance] (0.05) between the average scores of the experimental group that were studied according to the educational design based on the dimensions of human development and the average scores of the control group that was studied according to the usual method in the scale of environmental culture There are no statistically significant differences at the level of significance (0.05) between the average scores of the experimental group that were studied according to the educational design based on the dimensions of human development and the average scores of the control group that was studied according to the usual method in the scale of skillful thinking In order to verify the validity of these two hypotheses, the two researchers designed an educational design for an experiment that took a full course. The research sample was represented by students of the fourth year of middle school of Baghdad College High School divided into two divisions, each division (35) students for the experimental group that was studied according to the educational design built according to the dimensions of human development and (35) A student of the control group that studied in the usual way and the two groups were rewarded according to variables (intelligence, age, previous information, scientific culture scale, skillful thinking) The two researchers prepared the two research tools represented by the Scientific Culture Scale, which consists of (30) items, and the second tool, which is the Smart Thinking Scale, which consists of (30) items. By using the T-selection of two independent, equal samples, the results showed the superiority of the experimental group students over the control group’s students in both the scales of scientific culture and subtle thinking, and thus the two zero hypotheses were rejected for the research.